2012
DOI: 10.7809/b-e.00137
|View full text |Cite
|
Sign up to set email alerts
|

Database of Czech Forest Classification System

Abstract: Abstract:The Database of the Czech Forest Site Classification System (DCFCS; GIVD ID EU-CZ-002) is focused on data about ecological conditions and structure of forest ecosystems in the territory of the Czech Republic. This database is managed by Forest Management Institute Brandýs nad Labem. DCFCS consists of two parts, the numeric database and the GIS data. The numeric database includes all descriptive data of sample plots used in classification. Each plot is characterized by features of ecotope (information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The understanding of temporal patterns in biodiversity is limited by the availability of long-term, large-scale and high-resolution data (Dornelas et al , 2013). The data stored in the Database of Czech Forest Classification System have all these characteristics (Zouhar 2012). Moreover, our study showed that their resurvey provides results robust to location uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of temporal patterns in biodiversity is limited by the availability of long-term, large-scale and high-resolution data (Dornelas et al , 2013). The data stored in the Database of Czech Forest Classification System have all these characteristics (Zouhar 2012). Moreover, our study showed that their resurvey provides results robust to location uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…We resurveyed historical vegetation plots stored in the Database of Czech Forest Classification System (Zouhar, 2012). This database contains over 30 000 plots sampled with comparable methodology in the Czech Republic since the 1950s.…”
Section: Methodsmentioning
confidence: 99%
“…To explore temporal changes in the vegetation of sub‐montane forests, we resurveyed historical vegetation plots (Kapfer et al., ). The historical vegetation plots from the study region are available from a detailed study of regional forest vegetation (Pišta, ) and from the Database of Czech Forest Classification System (Zouhar, ). The aim of the original sampling was to document forest vegetation heterogeneity and to provide a basis for forest type classification (Pišta, ).…”
Section: Methodsmentioning
confidence: 99%
“…The Czech forest classification system database [48], managed by the Forest Management Institute, contains almost 49,000 vegetation records and over 25,000 environmental and soil observations and measurements collected throughout the country (78,000 km 2 ) since 1950's until 2007. Due to the subjective sampling design (explained above), there is no regular distribution of sampling plots within the Czech territory.…”
Section: Datamentioning
confidence: 99%